DRLC: A New Robust and Dynamically Load Balanced Clustering Scheme for Wireless Sensor Networks - Tellioglu, Ismail; Mantar, Haci A. (Springer-Verlag Berlin, 2010)
In this paper we present a robust and dynamically load bal- anced clustering scheme (DRLC) for wireless sensor networks. Firstly, we introduce a simple but effective dynamic and robust cluster head elec- tion protocol that makes decision based on the nodes' energy level and the number of neighbors. Since re-clustering is heavy and costly process, providing survivability of clusters in case of the cluster head (CH) failure is an important issue. To overcome this problem, we introduce a dynamic backup CH selection method that doesn't need global topology knowl- edge or extra nodes in the network. In case of CH failures this backup CH undertakes the CH's role and recovers cluster immediately. Secondly, we introduce a dynamic load balancing method to prevent overloading of CHs in network. When a CH's load increases, the CH sends a message to inform its members about the load so that some of these members may change their CHs. This decreases the loads of overloaded CHs and increases the lifetime of that cluster. The experimental results verify the achievement of our model.
2nd International Conference on Wireless and Mobile Networks -- JUN 26-28, 2010 -- Ankara, TURKEY
Keywords: Wireless sensor networks; clustering; load balancing; ro-bustness